The Role of Artificial Intelegensia Technology in Improving the Quality of Education - Wilda Susanti; Rahma Widi; Torkis Nasution; Johan Johan; Unung Verawardina (Journal of Applied Business and Technology, 2025)
The future of education is aligned with advances in artificial intelligence (AI) technology that significantly change how we learn, teach, and manage educational systems. This article reviews the critical role of AI technology in improving the quality of education in the digital era. AI technology allows for better personalization of education according to each student's needs and interests and changes how teachers teach and students learn. By using machine learning algorithms and data analysis learning algorithms and data analysis, education systems can identify patterns in student learning behavior, predict individual needs, and provide timely interventions. The article also highlights the challenges and opportunities in implementing AI technology in schools, including data privacy concerns, digital divides, and new skills required by educators. By understanding AI technology's role in improving education quality, we can design a more inclusive, responsive, and effective education system for a better future.